PENGARUH KELUARGA, ETNIS, KEPRIBADIAN, GENDER, DAN TEMAN SEBAYA TERHADAP MINAT BERWIRAUSAHA - Murwani Eko Astuti (STIE Wiyatamandala, 2021)
This paper investigates the factor which affected the student intention to be entrepreneur. The influences of family backround, ethnic, personality, gender and peer towards entrepreneurship are examined. Survey toward 88 students from four department in Faculty of Economics and Social, Universitas Jenderal Achmad Yani Yogyakarta were completed and regression analysis were employe to analyze the data. The result shows that personality and peer affected entrepreneur intention. Family background, ethnics, and gender are not important factor in influencing student intention to be entrepreneur as their career.